2019
DOI: 10.1186/s12889-019-7849-z
|View full text |Cite
|
Sign up to set email alerts
|

Associations between ambient air pollution and cancer incidence in Taiwan: an ecological study of geographical variations

Abstract: BackgroundAir pollution is a global public health concern. The World Health Organization has recently set up a goal of saving 7 million people globally by 2030 from air pollution related death. We conducted an ecological study of geographical variation to explore the association between air pollution (specifically, particulate matter <2.5 μm in aerodynamic diameter [PM2.5], particulate matter <10 μm in aerodynamic diameter, sulfur dioxide, nitrogen dioxide, nitric oxide, and ozone) and cancer incidence in Taiw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…Researchers have reported direct associations between PM2.5 levels and age-adjusted respiratory cancer incidence rates (30). The increasing lung cancer incidence rates in Iran are occurring along with increasing rates of environmental pollution, urbanization, and smoking (31).…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have reported direct associations between PM2.5 levels and age-adjusted respiratory cancer incidence rates (30). The increasing lung cancer incidence rates in Iran are occurring along with increasing rates of environmental pollution, urbanization, and smoking (31).…”
Section: Discussionmentioning
confidence: 99%
“…We consider monthly average PM2.5 concentration as a random effect in our model since this exposure indicator is a hierarchical factor rather than an individual one. Last but not least, an ecological study by Su et al presented the geographical variations on the association between PM2.5 and cancer incidence in Taiwan (Su et al 2019). Su et al also reported a significant 273 dose-response relationship between PM2.5 and OC incidence with spearman correlation ranged between 0.56~0.59 in men.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…At present, advanced countries are replacing traditional gasoline scooters with electric scooters that feature "low noise, zero emissions, energy savings, and environmental protection" as an important policy in industrial and environmental development. In Taiwan, scooters are one of the main causes of air pollution [9][10][11][12]. In this regard, the Environmental Protection Administration, Executive Yuan works for the EPA of Taiwan, not only continuously encourages manufacturers to produce environmentally friendly vehicles, but also publicizes the relative pollution emissions data of vehicles, and strives to improve urban air quality.…”
Section: Introductionmentioning
confidence: 99%